Exploring the well-being of professional female musicians: a self-determination theory perspective - Perrier, Laurence; Latreille-Gagné, Laurence; Khoriaty, Florence; Fortin, Maude; Bonneville-Roussy, Arielle (Frontiers in Psychology, 2025)
BackgroundThis study investigated the well-being of 16 professional female musicians through the lens of Self-Determination Theory, focusing on the satisfaction of their psychological needs for autonomy, competence, and relatedness, as well as the unique challenges they encounter in their careers.MethodsSemi-structured interviews were undertaken and analyzed using thematic analysis.Results and discussionThree broad themes and 10 sub-themes emerged from the interviews. The findings demonstrate that the well-being of female musicians is closely tied to the satisfaction of their psychological needs for autonomy, competence, and relatedness. Conversely, when these needs are frustrated, their well-being is negatively impacted. Other themes that emerged from the interviews are intrinsic motivation and the gender specific challenges within the music industry.ConclusionThe study highlights the need for supportive environments to enhance the well-being of female musicians (and performers as a whole), addressing both their psychological needs and the specific gender-related challenges they face.